Metodologia analítica para aminas bioativas como índice da autenticidade e da proporção de suco em refrigerante de laranja - Silvia Mendonca Vieira (2006)
THE POTENTIAL OF USING BIOACTIVE AMINES AND PROLINE TO DETERMINE THE AUTHENTICITY AND THE PROPORTION OF JUICE ADDED TO ORANGEPRODUCTS. The objective of this study was to investigate the potential of using bioactive amines and proline as an index of authenticity and of the proportion of juice added to orange products. An ion-pair-HPLC method was developed and validated for thedetermination of synephrine in orange products. Orange juice samples available in the market were characterized according to the levels of bioactive amines, proline and physico-chemical parameters. Nine amines were detected with three (synephrine, putrescine and spermidine) present in every sample analysed. The levels of aminesremained unchanged throughout the production of orange juice concentrate. The levels of synephrine did not change significantly throughout the harvest period. However significant difference was observed on the levels of proline, spermidine, on the brix/acidity ratio andon the acidity and pH. These results were similar in the three consecutive harvests. Based on these results, synephrine would be the most appropriate index for the detection of orange in orange products. An equation was proposed to estimate the amount of juice added to orange soft drink. In this equation, the levels of synephrine can be estimatedaccording to the brix/acidity ratio of the orange juice. Samples of soft drink from the market were analysed for synephrine. Only 43% of the samples contained the percent of orange juice stipulated by the Brazilian legislation according to the relation proposed betweensynephrine and orange juice content.